2017
DOI: 10.1016/j.ekir.2017.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Autonomic Neuropathy Predicts All-Cause and Cardiovascular Mortality in Patients With End-Stage Renal Failure: A 5-Year Prospective Study

Abstract: IntroductionChronic renal disease is associated with increased cardiovascular (CV) mortality. Cardiac autonomic neuropathy (CAN) is predictive of mortality for diseases that affect the autonomic nervous system. We prospectively evaluated the prognostic value of indexes of left ventricular (LV) function and CAN in all-cause and CV mortality of patients with end-stage renal failure (ESRF).MethodsA total of 133 patients with ESRF were recruited. LV function was evaluated by echocardiography, whereas cardiac auton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…These findings suggest that the possible cause of this association is sympathetic hyperactivity and a loss of parasympathetic regulation, which lead to an increase in the heart rate [ 79 , 80 ]. The high prevalence of CAN in type 2 diabetes, can synergize with the adverse effects on cardiovascular system induced by other common comorbidities such as hypertension, dyslipidemia and obesity [ 81 , 82 , 83 ] which contribute to premature morbidity and mortality [ 84 , 85 , 86 ]. In our review, the prevalence of erectile dysfunction was higher in type 2 diabetics.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that the possible cause of this association is sympathetic hyperactivity and a loss of parasympathetic regulation, which lead to an increase in the heart rate [ 79 , 80 ]. The high prevalence of CAN in type 2 diabetes, can synergize with the adverse effects on cardiovascular system induced by other common comorbidities such as hypertension, dyslipidemia and obesity [ 81 , 82 , 83 ] which contribute to premature morbidity and mortality [ 84 , 85 , 86 ]. In our review, the prevalence of erectile dysfunction was higher in type 2 diabetics.…”
Section: Discussionmentioning
confidence: 99%
“…At the five-year follow-up, the presence of CAN was found to be an independent predictor of all-cause and CV mortality. In addition to CAN, this study revealed that age, serum triglycerides, and left ventricular ejection fraction were independent risk factors for all-cause mortality in ESRD patients [ 30 ]. The results of our study add clinical evidence establishing cardiac dysautonomia testing as an effective risk stratification modality in patients with ESRD.…”
Section: Discussionmentioning
confidence: 99%
“…CAN is associated with worse outcomes of patients and a risk of cardiovascular disease (CVD) in a number of human pathologies. 2 , 3 …”
Section: Introductionmentioning
confidence: 99%
“…CAN is associated with worse outcomes of patients and a risk of cardiovascular disease (CVD) in a number of human pathologies. 2,3 CAN, which has a length-dependent pattern, is a common condition, but it is one of the most overlooked complications of endstage renal disease (ESRD). 3,4 The vagus nerve is responsible for approximately 75% of parasympathetic activity in humans and can be damaged in the early phase of CAN.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation